Optimal treatment approach for intracranial germinoma: a systematic review and meta-analysis - Zhirui Zhou; Jiabing Liu; Qi Yue; Lingxiao Chen; Xiwei Zhang; Xin Lin; Lin Zheng; Enmin Wang; Yang Wang; Ying Mao (BMC Cancer)
Abstract Background To determine the optimal treatment modality for intracranial germinoma (IG). Materials and methods A search of Medline, Embase, Web of Science and Cochrane Library was conducted up to April, 2024. Pooled risk ratio (RR) and 95% confidence interval (CI) were calculated. Subgroup analysis was applied according to radiotherapy (RT) alone or with chemotherapy (CTx). Results Total 37 studies were included in systematic review. Most IG patients were treated with biopsy or resection followed by RT with or without CTx. Prognosis of IG patients with different surgical resection is similar. Meta-analyses demonstrated focal field RT were with higher recurrence rate compared with craniospinal irradiation (CSI) [RR = 7.128, 95% CI (5.083, 9.995)], whole-brain RT (WBRT) [RR = 4.094, 95% CI (2.923, 5.735)] or whole-ventricle RT (WVRT) [RR = 3.361, 95% CI (2.126, 5.312)]; both WBRT and WVRT were also with higher recurrence compared with CSI; but no significant difference in recurrence and mortality between WVRT and WBRT. Total 24 studies reported treatment-related acute and/or late toxicity, combination CTx increased acute toxic, and expanded RT field and/or dose increased late toxicity. Conclusion Based on our findings, focal field RT is not recommended regardless of whether combined with CTx for intracranial pure germinoma. Although CSI is associated with better local control than other reduced-field RT, considering the potential toxicity and pattern of relapse, whole ventricles irradiation is more reasonable for localized or nonmetastatic germinoma. Reduced-dose CSI with or without chemotherapy is effective in metastatic or disseminated IG.